Markers of endothelial damage in children with diabetic ketoacidosis - Yu. V. Bykov; A. P. Vorobyova; V. A. Baturin; V. V. Massorov; J. S. Aksenova; G. A. Avakian (Вестник анестезиологии и реаниматологии, 2025)
Background. Diabetic ketoacidosis (DKA) is a common acute complication of type 1 diabetes (T1D) in children and adolescents that requires urgent hospitalization in an intensive care unit. DKA can lead to endothelial dysfunction (ED), but the diagnostic criteria for this condition have not been well studied in this urgent condition. The objective was to evaluate the severity of ED in children with T1D based on the degree of DKA by analyzing markers of endothelial glycocalyx (EGL) destruction in blood serum. Materials and methods. 60 children and adolescents aged 9–14 years were studied, of which 30 patients had T1D decompensation (DKA) and were included in Group I, conditionally healthy children were included in Group II. Patients with DKA were further divided into three subgroups based on the severity of clinical manifestations: 1st (severe, n = 5), 2nd (moderate, n = 16), 3rd (mild, n = 9). The concentrations of syndecan-1 (CD1 ), syndecan-4 (CD4 ), endocan-1 (EC1 ), heparin sulfate (HS), hyaluronic acid (HA), and angiopoietin-1 (AP1 ) were measured in blood serum using enzyme immunoassays. Results. An increase in four of the six studied markers of EGL degradation (CD1 , HS, HA, and AP1 ) was observed in patients at the stage of T1D decompensation compared to the control group. In the subsequent division of the study group, the highest concentrations of CD1 , CD4 , HS, HA, and AP1 were found in patients with severe DKA, with a decrease in average values for less severe clinical manifestations.Conclusion. High levels of the markers of EGL destruction (CD1 , HS, GC, and AP1 ) indicate the presence of ED in children with T1D at the stage of disease decompensation. The severity of ED is related to the clinical severity of DKA.